Long term outcome of secondary glaucoma following vitreoretinal surgery. Issue 3 (20th February 2004) - Tranos, P; Asaria, R; Aylward, W; Sullivan, P; Franks, W
Abstract : Purpose: To determine the long term outcome of secondary glaucoma following retinal reattachment surgery. Method: A longitudinal retrospective study was undertaken of the medical records of patients referred to the Glaucoma Service at Moorfields Eye Hospital following retinal reattachment surgery. The main outcome measures were final intraocular pressure (IOP), progression in cup:disc ratio, and final visual acuity outcome. Results: A total of 70 eyes of 70 patients (41 males and 29 females) were identified and included in the analysis. Mean increase of IOP 2–3 weeks following the first vitreoretinal procedure was 6 (SD 3) mm Hg. After a mean follow up of approximately 4 years the mean IOP had significantly decreased from 33 (SD 10) to 16 (SD 8) mm Hg (p<0.001). The visual outcome of eyes with final IOP less than 6 or greater than 21 mm Hg was significantly worse compared with those eyes with a normal (6–21 mm Hg) range of pressure (p = 0.022 and p = 0.009 respectively). Despite the effective control of IOP in the majority of patients during the follow up period, there was mild progression of the mean vertical cup:disc ratio from 0.6 (SD 0.2) to 0.7 (SD 0.2) (p<0.001). Conclusion: Secondary glaucoma is a major complication following retinal reattachment surgery. Medical treatment is successful in lowering IOP in most patients. In persisting cases surgical treatment is very effective, however it can be associated with an increased risk of postoperative hypotony. Despite apparently adequate IOP control there may be progressive cupping of the optic disc.